Cellular immune response to acute exercise: Comparison of endurance and resistance exercise. (15th April 2020) - Schlagheck, Marit Lea; Walzik, David; Joisten, Niklas; Koliamitra, Christina; Hardt, Luca; Metcalfe, Alan J.; Wahl, Patrick; Bloch, Wilhelm; Schenk, Alexander; Zimmer, Philipp
Abstract: Objectives: Exercise‐induced cellular mobilization might play a role in treatment and prevention of several diseases. However, little is known about the impact of different exercise modalities on immune cell mobilization and clinical cellular inflammation markers. Therefore, the present study aimed to investigate differences between acute endurance exercise (EE) and resistance exercise (RE) on cellular immune alterations. Methods: Twenty‐four healthy men conducted an acute EE (cycling at 60% of peak power output) and RE (five exercise machines at 70% of the one‐repetition maximum) session lasting 50 minutes in randomized order. Blood samples were collected before, after and one hour after exercise cessation. Outcomes included counts and proportions of leukocytes, neutrophils (NEUT), lymphocytes (LYM), LYM subsets, CD4/CD8 ratio, and the clinical cellular inflammation markers NEUT/LYM ratio (NLR), platelets/LYM ratio (PLR), and systemic immune inflammation index (SII). Results: Alterations in all outcomes were revealed except for CD8 + T cells, CD4/CD8 ratio, NLR, and PLR. EE induced a stronger cellular immune response and provoked alterations in more immune cell populations than RE. SII was altered only after EE. Conclusion: An acute EE session causes a stronger mobilization of immune cells than RE. Additionally, SII represents an integrative marker to depict immunological alterations.